Evaluation of the results of MOTAKK hepatitis C virus RNA genotyping and hepatitis delta virus external quality assessment programs during 2015-2016 - Karataylı, Ersin; Soydemir, Ege; Aksoy, Zeynep Büşra; Kızılpınar, Mehtap; Altay Koçak, Aylin; Karataylı, Senem Ceren; Yurdcu, Esra; Yıldırım, Umut; Güriz, Haluk; Bozdayı, Gülendam; et al. (Turkish Journal of Gastroenterology, 2019)
Background/Aims: To evaluate the HCV RNA genotyping and HDV RNA tests that are performed in molecular microbiology laboratories in Turkey as part of a national external quality assessment programme, MOTAKK (Moleküler Tanıda Kalite Kontrol) (English translation: Quality control in molecular diagnostics). Materials and Methods: Plasmas having different HCV RNA genotypes were used to prepare HCV genotype control sera. The HDV RNA main stock was prepared from patients with chronic delta hepatitis who had a significant amount of viral load detected, as per the WHO reference materials on viral load studies that were compiled for the purpose of developing HDV RNA control sera. Samples with different viral loads were prepared from this main stock by dilution. The prepared controls were delivered to the registered laboratories. The laboratories carried out the relevant tests and entered their results via the MOTAKK web page. External quality assessment (EQA) reports of the participants were uploaded to the website as well. Results: In total, there were 23 participating laboratories, out of which 20 exclusively performed HCV genotyping, and 15 and 16 only performed HDV RNA in 2015 and 2016, respectively. The success rate of the results of the HCV genotype was 56-96% in 2015 and 30-95% in 2016. The tube with a 30% success rate had a recombinant type of HCV, therefore, it could not be detected in most of the laboratories. The HDV RNA results were evaluated qualitatively. Accordingly, HDV RNA detection rates of participant laboratories were 71-100% in 2015 and 50-100% in 2016. Conclusion: This study was the first national external quality control program in Turkey regarding HCV RNA genotyping and HDV RNA in the field of molecular microbiology, and it was implemented successfully.